Simulation of burst aggregation and signalling schemes for optical burst switched networks - Dumych, Stepan; Maksymyuk, Taras; Guskov, Pavlo (Видавництво Львівської політехніки, 2013)
In this paper the model of IP-packet aggregation in the ingress node for OBS networks proposed. The main difference of this model is packet loss probability accounting due to block sizes distribution. Simulation results determined that proposed algorithm 10 times reduces the IP-packet losses, providing the same throughput.
Keywords: IP; Optical Burst Switching; Burst Header Packet; Intermediate Node Initiation